2018
DOI: 10.1002/jsfa.8924
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genetic background on the stability of sunflower fatty acid composition in different high oleic mutations

Abstract: The NM1 mutation is the best option to develop ultra-high oleic sunflower oil that is stable across environments and genetic backgrounds, making its agronomical production more efficient and predictable. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…NM1 mutants show a DNA insertion in the FAD2‐1 gene producing a premature stop codon (Alberio et al, 2016; Zambelli et al, 2015). Comparison of near isogenic lines with NM1 and Pervenets mutations, showed that lines bearing NM1 have a superior performance evidenced by higher percentage of oleic acid (up to 92%), lower percentage of linoleic acid (as low as 1%), almost undetectable linolenic acid content (lower than 0.3%), more stable fatty acid profile across environments, and low or even no‐dependence on the genetic background (Alberio et al, 2018) (Table 1). NM1 affects the coding region of the FAD2‐1 gene, while Pervents interferes with its transcription to an extent that does not depend solely on the presence of this mutation.…”
Section: Replacing Trans Fatty Acids (Tfa) In Food Processingmentioning
confidence: 99%
“…NM1 mutants show a DNA insertion in the FAD2‐1 gene producing a premature stop codon (Alberio et al, 2016; Zambelli et al, 2015). Comparison of near isogenic lines with NM1 and Pervenets mutations, showed that lines bearing NM1 have a superior performance evidenced by higher percentage of oleic acid (up to 92%), lower percentage of linoleic acid (as low as 1%), almost undetectable linolenic acid content (lower than 0.3%), more stable fatty acid profile across environments, and low or even no‐dependence on the genetic background (Alberio et al, 2018) (Table 1). NM1 affects the coding region of the FAD2‐1 gene, while Pervents interferes with its transcription to an extent that does not depend solely on the presence of this mutation.…”
Section: Replacing Trans Fatty Acids (Tfa) In Food Processingmentioning
confidence: 99%
“…These genotypes are selected and are allowed to grow under sub-lethal conditions. The genotypes giving good performance i.e., survivability, maximum root and shoot lengths are selected and are separated from the entire genotype sets (Alberio et al, 2018). High temperatures are induced by using TIR protocol in which temperatures to a maximum level and control in humidity can be done (Sudhakar et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Other high oleic sunflower mutants have been recently reported, for example one carrying the mutation named 29066 or NM1, which showed higher stability and reduced influence of genetic background. This mutant was less affected by environmental factors and the mutation was proved to be more effective to produce ultra-high oleic lines (Alberio et al, 2018).…”
Section: Introductionmentioning
confidence: 98%